2013
DOI: 10.1103/physreva.87.022709
|View full text |Cite
|
Sign up to set email alerts
|

Ionic fragmentation of the CO molecule by impact of 10-keV electrons: Kinetic-energy-release distributions

Abstract: The ionic fragmentation of a multiply charged CO molecule is studied under impact of 10-keV electrons using recoil-ion momentum spectroscopy. The kinetic-energy-release distributions for the various fragmentation channels arising from the dissociation of CO q+ (q = 2-4) are measured and discussed in light of theoretical calculations available in the literature. It is observed that the present kinetic-energy-release values are much smaller than those predicted by the Coulomb explosion model. The kinetic-energy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The excited molecular states prompted by the photoabsorption can follow several fragmentation pathways producing moieties with distinct translational energies following the rules of the fragmentation dynamics, obeying momentum and energy conservation laws. In this context, KER analysis, constituting a probe of the molecular fragmentation of the charged system, is of basic interest for understanding the structures of the moieties concerning the fragmentation dynamics and provides information on the excited states, on the character of repulsive states in the fragmentation process, and on the electronic states and potential energy functions. …”
Section: Introductionmentioning
confidence: 99%
“…The excited molecular states prompted by the photoabsorption can follow several fragmentation pathways producing moieties with distinct translational energies following the rules of the fragmentation dynamics, obeying momentum and energy conservation laws. In this context, KER analysis, constituting a probe of the molecular fragmentation of the charged system, is of basic interest for understanding the structures of the moieties concerning the fragmentation dynamics and provides information on the excited states, on the character of repulsive states in the fragmentation process, and on the electronic states and potential energy functions. …”
Section: Introductionmentioning
confidence: 99%
“…The KER spectrum for CO 3+ fragmentation can be compared with previous experimental investigations. The most probable KER value depends on the choice of projectile and values ranging from 11 eV to 27 eV have been reported for channel 1 [12,28,46]. For channel 2 the most probable KER value is generally higher than that for channel 1.…”
Section: Dissociation Of Co 3+ and N O 3+mentioning
confidence: 97%
“…The advent of recoil ion momentum spectrometer (RIMS) [5,6], along with position sensitive detector allows for detailed investigation of the subsequent molecular fragmentation process. In the past couple of decades, there have been extensive studies on the dissociation dynamics of multiply charged molecular ions produced in collisions with heavy ions [5][6][7][8], electrons [9][10][11][12] and photons [13,14]. Although, the target molecules under investigation range from diatomic molecules to polyatomic systems including large bio-molecules and PAHs (poly-cyclic aromatic hydrocarbons) it is the diatomics which have been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…3). Coulomb explosion from these dicationic states was studied previously by EUV 35,36 and soft-X ray 33,37 single-photon ionization as well as by electron 38,57,58 and ion 43,59,60,61 impact ionization. The Auger electron-ion coincidence spectroscopy 37 showed that the Coulomb explosion CH component on the higher energy side forming a long tail extending up to B10 eV.…”
Section: A H + + Ch 3 + Pathwaymentioning
confidence: 99%
“…A possible scenario will be discussed in the next subsection. 38,57,58 and ion 43,60 impact studies on methane. The KER spectrum in Fig.…”
Section: +mentioning
confidence: 99%